DISHARMONY IN THE REGULATION OF ZAKAT AS A TAX DEDUCTION FROM THE PERSPECTIVE OF ACEH’S SPECIAL AUTONOMY REGION OF INDONESIA - Nabillah Izzati; Armiadi Musa; Husni bin Abdul Ajalil (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2026)
The differences in zakat regulation between the national taxation system and the Aceh legal system raise significant legal and fiscal issues, particularly regarding the mechanism for its deduction from income tax. Within the national legal framework, zakat is positioned as a tax deduction from taxable income, as stipulated in the Income Tax Law and its implementing regulations. Conversely, Article 192 of Law Number 11 of 2006 concerning the Government of Aceh places zakat as a tax credit, as part of Aceh’s special status in the application of Islamic law. This study aims to analyse the position of zakat in both legal regimes and examine the implications of regulatory disharmony and the absence of implementing regulations on the effectiveness of zakat as a fiscal instrument. The research method used is normative legal research with a legislative, conceptual, and comparative approach. The results of the study show that the differences in zakat deduction mechanisms are substantive, as they are based on distinct tax calculation structures and produce distinct fiscal impacts on taxpayers. Furthermore, Article 192 of the Aceh Government Law remains normatively valid as lex specialis and cannot be limited by Government Regulation No. 60 of 2010. However, in practice, the two mechanisms for reducing zakat as income tax deductions have not been implemented at all due to the lack of harmonisation of regulations and adequate administrative mechanisms.